Immune Response of Mormon Crickets That Survived Infection by Beauveria bassiana - Robert B. Srygley; Stefan T. Jaronski (Psyche: A Journal of Entomology)
Beauveria bassiana (Fungi: Ascomycota) is an entomopathogenic fungus that serves as a biological control agent of Mormon crickets Anabrus simplex Haldeman (Orthoptera: Tettigoniidae) and other grasshopper pests. To measure the dose-dependent response of Mormon crickets to fungal attack, we applied B. bassiana strain GHA topically to adults using doses of 5.13 × 104 to 1.75 × 106 conidia in sunflower oil, with oil only as a control. After three weeks, we assessed the survivors' hemolymph for fungal cells, active phenoloxidase (PO), and lysozyme. Mortality increased and body mass of survivors decreased with conidial dose. survivors' PO activity was elevated to the same level independent of dose. Those with fungal cells visible in their hemolymph did not differ in PO activity from those with clear hemolymph. We conclude that circulating PO may be an important enzymatic defense against Beauveria infection and that it is associated with attempted clearing of Beauveria blastospores and hyphae from Mormon cricket hemolymph.